Contested and nervous spaces: exploring the environment of healthcare provision for international migrants in the Gauteng province of South Africa - Janine A. White; Laetitia C. Rispel (Taylor & Francis Group, 2024)
Background Notwithstanding the global goal of inclusive universal health coverage, and the notion of migrant-sensitive health systems, limited healthcare access or the exclusion of migrants from national health systems persists. South Africa has a rights-based constitution, but there is an inability or a failure of the health system to recognise and address the health needs of migrants. Objective To explore the intersection of the environment of healthcare provision for migrants and the everyday practices and behaviours of health workers and patients in the Gauteng province of South Africa. Methods The conceptual frameworks of health system responsiveness and social exclusion informed this institutional ethnographic study at 13 healthcare facilities in Gauteng province. We developed an observation guide to explore the intersection of culture and environment and its influence on healthcare provision to patients, especially migrants. Following ethics approval, we observed the facilities for 234 person-days. We used thematic analysis to analyse the data. Results Busy, frantic or nervous spaces, and contestations between patients and health workers, and among health workers formed part of the social and cultural environment of healthcare provision. The presence of migrant patients during busy periods served as a detonator for rude or discriminatory remarks, exacerbated by staff shortages and language barriers. Simultaneously, migrants exercised their agency by rebutting or confronting rude health workers. We also observed encouraging examples of kindness, caring and professionalism of health workers. Conclusion The study has implications for achieving a migrant-sensitive health system in South Africa.